2016
DOI: 10.1016/j.socscimed.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health and gender: The role of social norms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 44 publications
3
43
1
3
Order By: Relevance
“…The study is strengthened by the use of a closely matched control group, allowing us to take into account preexisting characteristics of mothers and fathers, and the use of prospectively recorded registry data. This enabled us to investigate previously indicated patterns found in studies using selfreported data [7,8], which contrary to registry-based studies are subject to recall bias and bias of men being less inclined to report ill health than women [19]. A potential limitation of registry-based data concerns information bias such as over-or under coverage and incomplete or inaccurately recorded data.…”
Section: Discussionmentioning
confidence: 99%
“…The study is strengthened by the use of a closely matched control group, allowing us to take into account preexisting characteristics of mothers and fathers, and the use of prospectively recorded registry data. This enabled us to investigate previously indicated patterns found in studies using selfreported data [7,8], which contrary to registry-based studies are subject to recall bias and bias of men being less inclined to report ill health than women [19]. A potential limitation of registry-based data concerns information bias such as over-or under coverage and incomplete or inaccurately recorded data.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that older individuals often overestimate their health [35], possibly due to peer effects [36]. Some evidence suggests that women tend to underestimate their health [9], which could be related to them reporting limitations more frequently [37][38][39]. However, other studies find no effect of gender on reporting behaviour [15].…”
Section: Determinants Of Concordancementioning
confidence: 99%
“…Moreover, older women were shown to act as caregivers for their ill husbands and to suffer negative consequences for their mental and physical health (Schrank et al, 2016). Previous studies reported a gender related disparity in health with either women (Caroli & Weber-Baghdiguian, 2016) or men (Lipsky, Cannon, Lutfiyya, 2014) at disadvantage concerning health in old age (Bird & Ricker, 2008). Furthermore, aging itself might be experienced in different ways according to one's gender (Connell, 2012).…”
Section: Gender Equality In Health and Agingmentioning
confidence: 98%